Imaginarios sociales sobre la sexualidad: un estudio de la vida cotidiana de los estudiantes de la carrera de Sociología de la UEB, Guaranda, 2022. - Tixi Lucio, Lisseth Estefania (2023)
The research work presented below addresses the issue of sexuality and how it is perceived by the students of the Sociology career of the State University of Bolívar through the social imaginaries present in this population, which were analyzed based on to the information collected through the mixed method, carrying out a bibliographic compilation on sexuality seen from a social approach by authors such as Michel Foucault and Niklas Luhmann to later carry out surveys, which are divided into three categories: Sexuality, Daily Life and Imaginaries. on Sexuality, were applied to 209 students who voluntarily participated in this research. Within the surveys, factors such as the influence of religion and culture and their relationship on the behavior of individuals in the face of certain activities associated with sexuality present in their daily life were analyzed, a term that refers to those activities or actions that they carry out. individuals on a daily basis. The objective of this research was to identify those traditional social imaginaries about sexuality that are still valid in students. The surveys were applied to the students of the sociology career within the period August 2022 - September 2022, who have a predominant age range of 20 to 25 years. It sought to investigate how their beliefs, cultures and different social environments play a fundamental role when discussing the power that is exercised within decision-making in relation to their sexuality, how they live and understand it within the community educational. Traditional social imaginaries are present in the way in which students perceive sexual diversity while a change is evident in the way of understanding and seeing sexuality, untying reproduction and strengthening identity, gender and sexual preferences to This concept. It is highlighted that the reproduction of taboos, myths, stigmas and religious beliefs that influence the behavior of students in relation to the conduct and attitudes they take towards everything that breaks with heterosexual hegemony is still in force.Keywords: Social Imaginaries, Youth, Sexuality, Perception, Daily Life